Inventory-production control systems with Gumbel distributed deterioration - Baten, Md Azizul; Kamil, Anton Abdulbasah; Lateh, Habibah (Elsevier B.V., 2012)
This paper is concerned with the optimal control of inventory-production system subject to Gumbel distributed deterioration items with applications to optimal control theory.We successfully formulated the model as a linear optimal control problem and obtained an explicit solution using Pontryagin maximum principle.The optimality conditions are derived in this case. It is then illustrated with the help of examples.